HIF-2α drives osteoarthritis progression via suppression of the HDAC4-ATF4-CHOP signaling axis - Pinpin Jiang; Hang Wang; Yujia Li; Yuanyu Zhang; Jingrui Huang; Yukun Xu; Dahai Rong; Danni Ruan; Yao Wang; Jie Yuan; Pengcui Li (PLoS ONE, 2026)
Hypoxia-inducible factor-2α (HIF-2α) is a key regulator of cellular adaptation to hypoxia, but its role in osteoarthritis (OA) remains incompletely defined. This study aimed to investigate the contribution of HIF-2α to OA pathogenesis and the underlying molecular mechanisms. Human cartilage specimens were collected to examine HIF-2α expression and components of the histone deacetylase 4 (HDAC4) signaling pathway using Western blotting, quantitative real-time PCR, and immunohistochemistry. An in vitro OA model was established in chondrocytes using interleukin-1β (IL-1β), followed by HIF-2α knockdown with small interfering RNA and overexpression via adenoviral transduction. Chondrocyte apoptosis was assessed by flow cytometry and TUNEL staining. To evaluate in vivo effects, HIF-2α was silenced using an adeno-associated viral vector in a rat OA model induced by anterior cruciate ligament transection (ACLT). Disease progression was assessed by X-ray, computed tomography (CT), FMT® small animal in vivo fluorescence molecular tomography imaging system, Safranin O staining, and immunohistochemistry. HIF-2α expression was significantly increased in cartilage from OA patients and ACLT rats. In vitro , HIF-2α modulation altered HDAC4 expression and downstream apoptotic signaling. Knockdown of HIF-2α reduced chondrocyte apoptosis and attenuated cartilage degeneration in vivo . These findings indicate that HIF-2α promotes OA progression by regulating chondrocyte apoptosis and matrix homeostasis through the HDAC4-ATF4-CHOP pathway. This study identifies a previously unrecognized mechanism linking HIF-2α to OA and highlights its potential as a therapeutic target.